Hansen’s disease: Is histopathological correlation mandatory for all clinically diagnosed patients? A descriptive study in a tertiary care hospital - Sananda Koley,; Nandini Das,; Sunita Bagdi,; Sritanu Jana,; Surajit Dolui,; Sanjay Sengupta, (Asian Journal of Medical Sciences, 2024)
Background: Leprosy has been historically associated with social stigma and discrimination. Leprosy, also known as Hansen’s disease, is indeed a chronic infectious disease caused by the bacterium Mycobacterium leprae. Diagnosis of leprosy is usually done by clinically and classified as multibacillary (MB) and paucibacillary (PB). The disease was also classified into different types based on histopathological findings, such as tuberculoid, borderline tuberculoid (BT), mid-borderline, borderline lepromatous, and lepromatous. Aims and Objectives: The aim of the study was the clinicohistopathological correlation of all clinically diagnosed cases of Hansen’s disease. Materials and Methods: The study was done at Bankura Sammilani Medical College and Hospital for a period of 18 months. Ethical approval was taken from the Institutional Ethics committee. All new patients 66 in number clinically diagnosed as leprosy attending the Dermatology Outpatient Department were included in the study. The skin biopsy and staining were done with hematoxylin and eosin staining and Fite-Faraco stain for every patient. The skin biopsy was reported according to the Ridley-Jopling classification. Results: Males were more commonly affected than females. Most of the leprosy cases in the study were classified as MB (86.4%) and the upper extremities were the most commonly affected sites. Bacterial index was observed negative in clinically PB cases. The most common histological subtype of leprosy identified in the study was BT, Regarding bacterial index, all clinically diagnosed MB cases were smear positive and PB cases were smear negative. Out of nine clinically diagnosed PB cases, inflammatory cells were found in 3 (33.4%). Conclusion: In a large country like India where resources are limited, no need for skin biopsy for every patient. Biopsy should do if there is any confusion with other skin lesions.